2019
DOI: 10.1590/0034-7167-2017-0871
|View full text |Cite
|
Sign up to set email alerts
|

Nurse researchers and nursing assistants: construction and projection of polymorphous identities

Abstract: Objective: To understand the meanings that nurse researchers and nursing assistants attribute to one another, and to the development of research produced by Nursing. Method: Qualitative research. The Grounded Theory and the Complexity Theory were used as theoretical and methodological frameworks, respectively. Ten nursing assistants and six research nurses participated in the research. The semi-structured interview was used as a data collection technique. The results were categorized by comparative analysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
(30 reference statements)
0
1
0
2
Order By: Relevance
“…Chaffee and McNeill (2007) displayed the connection between CAS and the metaparadigm of nursing based on the four consensus concepts: human being, nursing, health and environment. One study also revealed the distant realities that emerge from the same system when scientific research and the nursing care dimension are used in an attempt to bridge gaps in the science of nursing (Silva, Silva, Lins, Silva, & Leite, 2019). White and Begun (1996) visualized the nurse profession as a CAS.…”
Section: Resultsmentioning
confidence: 99%
“…Chaffee and McNeill (2007) displayed the connection between CAS and the metaparadigm of nursing based on the four consensus concepts: human being, nursing, health and environment. One study also revealed the distant realities that emerge from the same system when scientific research and the nursing care dimension are used in an attempt to bridge gaps in the science of nursing (Silva, Silva, Lins, Silva, & Leite, 2019). White and Begun (1996) visualized the nurse profession as a CAS.…”
Section: Resultsmentioning
confidence: 99%
“…Além disso, a pessoa cuidada costuma ter o apoio familiar (ou a falta dele). Assim, a família é mencionada com muita frequência nas experiências dos enfermeiros como fator chave na determinação da complexidade do cuidado (Silva et al, 2019;Carlos et al, 2017;Guarinoni et al, 2015).…”
Section: Classe 1 O Paradigma Da Complexidade E Os Cuidados De Enfermagem Diante As Adversidades Da Assistênciaunclassified
“…Outros estudos abordaram aspectos sobre a saúde do adolescente, principalmente em relação à sexualidade, infecções sexualmente transmissíveis (IST) e a busca pela autonomia (Huang et al, 2019;Silva et al, 2019;Carvalho, Erdmann & Santana, 2015;Silva et al, 2015;Miller et al, 2010).…”
Section: Classe 2 Complexidade Dos Cuidados Nas Fases Da Infância E Adolescênciaunclassified